Problem-Based Learning (PBL) Physics Teaching Books Newton’s Gravity Force - Rahmawati, Novi; Azizah, Auliatul; Salsabila, Nabila; Sholehatennafiah, Vivi; Fadah, Hanim Isti; Safitri, Riya; Kaneishia, Sabrina; Mayasari, Sinta; Mahmudyah, Niken Noviana; Subiki; Mahardika, I Ketut (AMPLITUDO : Journal of Science and Technology Innovation, 2024)
The purpose of this research is to test the validity and feasibility of physics textbooks that have been developed based on Problem Based Learning (PBL) on Newton's gravitational force material. This research uses development research methods. The validation sheet is used as a research instrument. The validation sheet was validated by two experts and declared valid according to predetermined criteria. Textbook validation data was collected from two experts, one textbook media expert and one physics material expert. There are two aspect criteria that are tested for validity, the form of dialogical and interactive presentation of language and the contextual nature of textbooks. The purpose of this research approach is to describe the effectiveness, validity and feasibility of using physics textbooks. The research results obtained are the percentage of aspects of dialogic and interactive language validation as well as aspects of contextual nature that have been tested by material experts obtained an average percentage of 87.5%, which means that the physics textbooks that have been developed are included in the feasible criteria. The results of the research tested by media experts on aspects of dialogic and interactive language as well as on aspects of contextual nature both obtained an average percentage of 100%. This means that a physics textbook based on Problem Based Learning (PBL) on Newton's gravitational force is very feasible to be tested based on validity testing by one material expert and one media expert.